(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Urothelial carcinoma is the most common neoplasm of urinary bladder. Antigen Ki-67 is a nuclear protein that is necessary for cellular proliferation. The aim of this study was to determine the association of expression of Ki-67 with histopathological parameters in radical cystectomy specimens of histologically diagnosed cases of infiltrating urothelial carcinoma. This is a cross-sectional study conducted among 36 cases of infiltrating urothelial carcinoma collected from Department of Pathology, Bangabandhu Sheikh Mujib Medical University. Histopathological parameters i.e. morphologic variants, stage (pT), lympho-vascular invasion, perineural invasion and lymph node metastasis were assessed. Ki-67 immunohistochemistry were performed. Mean ±SD age of the patients was 58.9±13.8 years. Among the morphological variants, 64% cases were microscopically arranged in papillary pattern. Eighteen (50%) patients underwent surgical intervention at stage pT2. Lympho-vascular invasion, perineural invasion and lymph node metastasis were identified in 12 (33.3%), 9 (25%) and 13 (48.1%) of the cases, respectively. Among the morphological parameters, Ki-67 shows association with pathological stages and lymph node metastasis. The use of Ki-67 immunomarker along with grading and staging may provide significant prognostic information in urothelial carcinoma of the urinary bladder. BSMMU J 2022; 15(3): 186-191